Output currents of VSI with economic DC link supplying induction motor - Klytta, Marius; Korotyeyev, Igor (НТУ "ХПИ", 2014)
This paper deals with spectral analysis of currents of asynchronous motor fed from voltage source inverter with very small capacity in the DC link. It allows the estimation of the torque and speed quality in smart drives using VSI with such economic DC link.
Keywords: induction motor; voltage source inverter; current harmonics; economic DC link